Pendugaan Potensi Maksimum Lestari dan Tingkat Pemanfaatan Ikan Tongkol (Euthynnus sp.), Ikan Layang (Decapterus sp.), dan Ikan Lemuru (Sardinella lemuru) yang didaratkan Nelayan di PPN Pengambengan, Kabupaten Jembrana - Suherman, Pande Made Ryan; Puspitha, Ni Luh Putu Ria; Dirgayusa, Gusti Ngurah Putra (Journal of Marine Research and Technology, 2025)
Fisheries are a key industrial sector in Indonesia, resilient during crises and contributing to food supply, income, and employment. The capture fisheries sub-sector plays an essential role, notably in Bali Province, which has 9,634.35 km² of marine waters and a 470 km coastline, with an estimated potential of 147,278.75 tons/year. Production is dominated by tuna, mackerel, and lemuru. Pengambengan Nusantara Fishing Port (PPN) in Jembrana serves as a major hub for marine fisheries, landing lemuru (76%), mackerel (18%), tuna (4%), and others (2%). However, fishermen lack knowledge of maximum allowable catches, threatening stock sustainability. This study aims to determine the CPUE (Catch per Unit Effort), MSY (Maximum Sustainable Yield), and utilization rates of tuna, mackerel, and lemuru landed at PPN Pengambengan using a quantitative descriptive method and the Schaefer model. Results show CPUE averages of 0.72 tons/fleet for tuna, 0.74 tons/fleet for mackerel, and 28.74 tons/fleet for lemuru, influenced by climate phenomena such as El Niño, La Niña, IOD, and overfishing. MSY estimates are 2,415.11 tons/year for tuna (Emsy 3,707.56 tons/year), 2,956 tons/year for mackerel (Emsy 5,703 tons/year), and 15,908 tons/year for lemuru (Emsy 13,647 tons/year), reflecting significant differences in sustainable potential and effort. Utilization rates range from 0.48% to 327.95%, indicating variability among species, though overall exploitation is considered optimal.